Decision-making as phase transitions in sport - Araújo, D.; Davids, K.; Rocha, L.; Serpa, S.; Fernandes, O. (International Journal of Computer Science in Sport, 2002)
Changes in the macroscopic order of a dynamical system are called phase transitions, and are based on a symmetry-breaking process (Kelso, 1995). Araujo et al (2003) showed that, in a typical 1 v 1 sub-phase of basketball, the distance between an attacker-defender dyad and the basket changed dramatically as a consequence of the attacker`s success in dribbling past the defender. Goal path selection in de-stabilising dyads formed with defenders was an emergent process for attackers. For this reason, goal path selection can be intentionally constrained but cannot be specified completely in advance. The results showed that the decision ``when to drive" to the basket by a successful attacker was an example of symmetry-breaking in a stable dyad. In the present study, we aimed to investigate whether the theoretical tenets of dynamical systems theory could be generalized to the sport of sailing. This study addressed how the local environment plays a large role in selecting functional behaviours. Athletes` decision making is a means of using active strategies that leave much of the information out in the context, and carefully using real-time sequences of body-world interactions to solve problems in a robust and flexible way. Solutions emerge from this interaction of organismic and contextual constraints. The purpose of a sailing regatta can be described as attempting to master the use of the wind in order to arrive at the finish line as quickly as possible. This goal must be obtained through performance manoeuvres that aim to control the direction and the speed of the boat. According to regatta rules, five decreasing minutes before the start, sailors initiate the so-called starting procedures in order to be in the optimal position (relatively to the wind) at the starting line ("second zero"). We expected to observe transition phases in the starting line location as a function of by manipulating the wind-line angle. We also expected to observe this phenomenon when participants started with and without adversaries.